Exploring the web with OXPath. - Furche, T; Gottlob, G; Grasso, G; Schallhart, C; Sellers, A (ACM, 2011)
OXPath is a careful extension of XPath that facihtates data extraction from the deep web. It is designed to facilitate the large-scale extraction of data from sophisticated modern web interfaces with client-side scripting and asynchronous server communication. Its main characteristics are (1) a minimal extension of XPath to allow page navigation and action execution, (2) a set-theoretic formal semantics for full OXPath, (3) and a sophisticated memory management that minimizes page buffering. In this poster, we briefly review the main features of the language and discuss ongoing and future work. Copyright 2011 ACM.